Bedaquiline- versus injectable-containing drug-resistant tuberculosis regimens: a cost-effectiveness analysis. (2nd November 2018) - Ionescu, Ana-Maria; Mpobela Agnarson, Abela; Kambili, Chrispin; Metz, Laurent; Kfoury, Jonathan; Wang, Steven; Williams, Abeda; Singh, Vikram; Thomas, Adrian
ABSTRACT: Background : Drug-resistant tuberculosis (DR-TB) continues to be a major public health challenge with suboptimal treatment outcomes including well-documented treatment-related toxicities. We compared the cost-effectiveness of bedaquiline (BDQ) containing regimens with injectable containing regimens (short-course regimen [SCR] and long-course regimen [LCR]) in India, Russia, and South Africa. Methods : The analysis evaluated the direct costs of DR-TB treatment which included drugs, hospitalization, injectable-related adverse event costs, and other costs. Scenarios altered regimen costs, SCR/LCR ratio, and substitution rate between regimens (whether BDQ or injectable containing). Results : BDQ containing regimens are more cost effective based on cost per treatment success compared with injectable containing regimens, reducing these in SCR by 18–20% and in LCR by 49–54%. Average cost effectiveness ratios (ACERs) of BDQ containing regimens are lower. The incremental cost effectiveness ratio (ICER) is negative. Exclusive use of BDQ containing regimens results in approximately 61, 000 more patients treated successfully over 5 years. Conclusions : Across all countries, BDQ containing regimens are dominant compared to injectable containing regimens, entailing lower treatment costs to achieve better clinical outcomes. This analysis can provide insight and support to local and global decision-makers and public health organizations to allocate efficiently resources improving patient and public health outcomes.